Epitope Mapping and Allergenicity Reduction of α-Amylase Inhibitor, a Typical Wheat Non-gluten Allergen - WANG Yao, ZHANG Qiaozhi, WANG Yanbo, FU Linglin (Shipin Kexue, 2023)
This study aimed at the epitope mapping and allergencity reduction of the wheat non-gluten allergen α-amylase inhibitor. Its linear epitopes were predicted by using bioinformatic prediction tools DNAstar, IMED, and IEDB. Six candidate epitopes were obtained by comprehensive analysis, and four linear epitopes were verified by using indirect competition enzyme-linked immunosorbent assay (ic-ELISA). The allergenicity of the allergen was reduced by interaction with polyphenols, A non-covalent complex of α-amylase inhibitor and epigallocatechin gallate (EGCG) was prepared and characterized by fluorescence spectroscopy, circular dichroism (CD) spectroscopy and ultraviolet (UV) spectroscopy, and the efficiency of allergenicity reduction was investigated by ic-ELISA. Results showed that the complex with a molar ratio of α-amylase inhibitor to EGCG of 1:30 had the lowest IgE-binding capacity. The binding capacity was reduced by 22.7%. Molecular docking simulations by using Autodock software further demonstrated that the allergenicity reduction was due to the interactions of the linear epitopes of α-amylase inhibitor and their nearby residues with EGCG. This study can provide a reference for the epitope mapping of wheat non-gluten allergens and the preparation of polyphenols to reduce their allergenicity.